Sequence of reading activities and linguistic analysis from a dialogical perspective with the discoursive genre apologue - Braga de Oliveira, Ecila; Ohuschi, Márcia Cristina Greco; Rodrigues, Isabel Cristina França dos Santos (The ESPecialist, 2024)
The objective of this article is to present a sequence of dialogical activities with the genre apologue “O toco de Lápis”, for 6th grade students at elementary school, mixing reading and linguistic analysis in the curricular component Portuguese Language. The theoretical-methodological actions are based on studies of Volóchinov (2021 [1929]; 2013[1930]), Bakhtin (2011 [1979]), Geraldi (2005[1984], 2013[1991]), Franchi (1991 [1987]), Polato (2017), Menegassi (2020), and Xx e Author 2 (2022). Therefore, the aim is to establish a dialogue with the basic education teacher about possibilities for expanding students’ sociological awareness, including reading skills, and reflection on linguistic elements in living and concrete utterances.